2021
DOI: 10.3389/feduc.2021.700441
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of School Support During COVID-19: What Satisfies Parents?

Abstract: During the COVID-19 pandemic lockdown, face-to-face schooling could not be performed continuously, and alternative ways of learning had to be organized. Parents had to act as their children’s home schooling tutors while working from home, and schools had to deal with various alternatives to distance education. Since parents are by all means both important school users and partners, their perceptions of schools can be considered a central indicator for assessing school quality. In this respect, during school lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 69 publications
1
16
0
2
Order By: Relevance
“…Parents were concerned with their children's learning [22,36] and distrustful of the educational institutions' capacity to address the situation with competence [36]. The perceived support and abilities of teachers were acknowledged, through a longitudinal study, to be the main predictors of parents' school satisfaction during the lockdown period [24].…”
Section: Parents and Emergency Remote Teaching And Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents were concerned with their children's learning [22,36] and distrustful of the educational institutions' capacity to address the situation with competence [36]. The perceived support and abilities of teachers were acknowledged, through a longitudinal study, to be the main predictors of parents' school satisfaction during the lockdown period [24].…”
Section: Parents and Emergency Remote Teaching And Learningmentioning
confidence: 99%
“…We also consider a contextualized analysis to be valuable, given the fact that not only the pandemic affected different parts of the world at different times and intensities, but also that national and local educational responses to schools' closings were not universal. This is also an underexplored point of view in international studies [21][22][23][24]. Additionally, there is a lack of research concerning online learning in the early years [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…They also had to deal with the motivational aspect in relation to their children (Garbe et al, 2020;Mak, 2021) or with the distractions that arose and were easily incorporated by the children, mainly the younger ones. In addition, considering the academic activities proposed, almost half of the parents agreed that they were very difficult to understand, either because they had almost total ignorance about the subject matter or simply because they did not have enough guidance to carry them out (Haller & Novita, 2021). The findings also show that mothers were the main responsible for following up their children's process in almost all cases of remote education at home, as suggested by other research (Aladsani, 2021;Bunga et al, 2021;Lau et al, 2021).…”
Section: Discussionmentioning
confidence: 74%
“…A study conducted in Germany by Haller and Novita (2021) found that parent perceptions of school support and educator abilities during distance education were especially relevant for parents’ levels of school satisfaction. Parents reported higher satisfaction when distance learning was implemented effectively, and if educators’ technical capabilities and the school’s technical infrastructures were up-to-par [ 126 ].…”
Section: Educationmentioning
confidence: 99%